Development Of Historical Animation Video On The Material Of The Proclamation Of Indonesian Independence For Senior High School - Najuah, N; Simarmata, Esra; Yohanna Marpaung, Cindy; Chinda Carolina Sembiring, Putri; Stip Angelina Sitanggang, Via (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This research aims to: (1) to know the steps in the development of historical video animation on the material of the proclamation of Indonesian independence in class XI SMA Negeri 1 Bandar Perdagangan and (2) to know the feasibility of historical video animation on the material of the proclamation of Indonesian independence in class XI SMA Negeri 1 Bandar Perdagangan. The method used in this research is the Research and Development (R&D) method with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The population of this study was students of class XI IPS SMA Negeri 1 Bandar Perdagangan, with samples taken from class XI IPS 1. Data were collected using a questionnaire. Tools used to collect data include validation from material experts, validation from media experts, and product trials for students. The data analysis technique used in this research is quantitative analysis. The results showed that the learning media in the form of historical animated videos developed obtained an assessment from material experts of 92.86% (very feasible category). In comparison, media experts assessed 92.24% (very feasible category). Product trials in small groups resulted in a score of 91% (very feasible category), and in large groups, obtained a percentage of 95% (very feasible category). From these results, it can be concluded that the historical animated video media developed is very suitable for use in history learning activities at school.